The Use of Group Work Based on Interest to Improve Students’ English Speaking Skill at SMA Negeri 3 Makassar - Navriansyah, Andi Muhammad Aidil; Baa, Sultan; Aeni, Nur (State University of Makassar, 2024)
This research aims to provide tangible evidence concerning the effectiveness of utilizing group work based on interest to augment English speaking skill among students at SMA Negeri 3 Makassar. Employing a quasi-experimental framework, data were gathered through pretest and posttest. The study encompassed tenth-grade students from SMA Negeri 3 Makassar, and sample selection employed random sampling, enlisting X-6 as the experimental group and X-8 as the control group. The experimental group underwent interest-based group work, while the control group received conventional instruction. Pretest findings unveiled a mean score of 64.55 for the experimental group and 64 for the control group. Following the treatment for both groups, a post-test was administered, yielding a mean score of 76.55 for the experimental group and 70.51 for the control group. Notably, data showed an atypical distribution yet were homogenized, which led to the hypothesis test was assessed through Wilcoxon and Mann-Whitney tests, facilitated by SPSS 22.0. Based form the test, The 2-tailed Sig. value of the test is .000 which is lower than alpha value of 0.05, indicating that there is significant improvement in speaking skill for high school students after using group work based on interest compared to the conventional method.Key words– Group Work, Interest, Speaking Skill.